Sexual behaviour and reproductive performance of zaraibi and damascus does as affected by different senses - Hadeer Mohsen Aboshady; Galal Eldin Muhammad Ashmawi; Mamdouh Sayed Abdalla (Cairo : Hadeer Mohsen Aboshady, 2012)
Twenty three Zaraibi and sixteen Damascus does were used to investigate the influence of tactile , olfactory and auditory stimuli of bucks on sexual behavior and LH secretion . Does of each breed were randomly allotted into four groups . Does of the first group served as a control . In the second group , does were joined by an intact male of the same breed (tactile group)
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture - Department of Animal Production
Issued also as CD
Keywords: Estrous behaviour; LH; Zaraibi